Composite pleomorphic xanthoastrocytoma-ganglioglioma; assessing and addressing the dilemma of differential expression of neuronal markers: Case report with diagnostic perspective - Kavita Gaur; Rakesh Kumar Gupta; Ravindra K Saran; Mehar C Sharma (Wolters Kluwer Medknow Publications, 2019)
We report the case of a 5-year-old male child presenting with seizures for 4 months. Magnetic resonance imaging (MRI) revealed a cortical-based solid cystic lesion in the right parietal lobe. Histopathological examination showed a tumour comprised of spindled glial fibrillary acid protein (GFAP) positive neoplastic cells interspersed with bizarre pleomorphic cells showing nuclear pseudoinclusions and intermingled dysplastic ganglion cells variably immunopositive for synaptophysin, chromogranin, Neu-N and immunonegative for neuron filament protein (NFP). This report highlights the occurrence of the rare composite pleomorphic xanthoastrocytoma-ganglioglioma and the vagaries of immunohistochemical analysis in highlighting neuronal differentiation in such a case setting. In addition, to the best of our knowledge this is the youngest patient till date to present with this entity.